The Ijen Coffee Plantation in an Innovative Science Module to Enhance Science Literacy in Elementary School - Nuriman; Rizki Putri Wardani; Agustiningsih; Arik Aguk Wardoyo; Rohma Novia Dini; Maulia Eka Nur Adillah; Afriansyah Prasetyo (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop and analyze innovative elementary school science learning module modules based on the Ijen Arabica Coffee agricultural. This study is a research and development (R&D) study that adapts the ADDIE model. Data was analyzed through validation score, practicaly, and N-gain effectivenes. Data collection instruments include expert validation sheets, teacher and student response questionnaires, and science literacy test questions. The results of the study show that: (1) The learning module was declared to be very feasible by expert validators in terms of content, media, and language, with an average score of 90.41%; (2) The module was declared to be highly practical by teachers about 91.50% and highly interesting for students about 91.50%; (3) The module significantly improved students' science literacy, as evidenced by an increase in the average score from 50.20 to 83.45. The N-Gain analysis results showed a score of 0.67 with moderate category. The Ijen Arabica Coffee-based module is not merely supplementary material, but rather an innovative tool that can change students' perceptions of science. It was concluded that this Ijen Arabica Coffee-based science teaching module is valid, practical, and effective for use as material for training contextual science literacy in elementary schools.